2021
DOI: 10.20884/1.jks.2021.16.1.1637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Five-Finger Relaxation Technique on Depression in Type 2 Diabetes Mellitus Patients

Abstract: Diabetes mellitus (DM) can cause physical and psychological changes for sufferers. Psychological changes include changes in self-concept and depression. Psychological changes can be treated with nonpharmacological therapies, one of which is five-finger relaxation technique. The research aimed to reveal the effect of five-finger relaxation technique on depression experienced by type 2 DM patients. The five-finger relaxation technique is one of the generalist relaxation techniques by recalling pleasant experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Pain is the main complaint most often experienced by cancer patients (6). Pain occurs as a result of cancer cell metastases (64%), treatment (33%), or caused by both (7,8). The American Cancer Society stated that pain experienced by cancer patients depends on the type of cancer, the stage of the cancer, and the pain threshold, it will have an impact on all dimensions of the quality of life of cancer patients (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain is the main complaint most often experienced by cancer patients (6). Pain occurs as a result of cancer cell metastases (64%), treatment (33%), or caused by both (7,8). The American Cancer Society stated that pain experienced by cancer patients depends on the type of cancer, the stage of the cancer, and the pain threshold, it will have an impact on all dimensions of the quality of life of cancer patients (14).…”
Section: Discussionmentioning
confidence: 99%
“…Pain is the main complaint most often experienced by cancer patients (6). Pain is caused by cancer cell metastases (64%), due to treatment (33%), or caused by both (7,8). Treatments that can trigger pain include chemotherapy, surgery, hormone therapy, and radiation therapy (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five-finger hypnosis is a psychological intervention that provides therapy treatment in a relaxed state and then focuses on memories or images while performing therapy. 46 Progressive Muscle Relaxation (PMR) is a form of non-pharmacological therapy that is commonly used in pain therapy for cancer patients. In this review, two articles were found that examined the effectiveness of this therapy.…”
Section: Case Studymentioning
confidence: 99%
“…A carbohydrate diet is a diet that reduces carbohydrate consumption and increases fat consumption as an energy source. When doing a carbohydrate diet, the body will burn fat, not carbohydrates (Dewi, et al, 2023). This condition is called ketosis.…”
Section: Introductionmentioning
confidence: 99%